Effects of water absorption and salt on discrimination of wheat gluten strength assessed by dough mixing and protein composition. (September 2019) - Isaak, Carly; Sapirstein, Harry; Wu, Yao; Graf, Robert
Abstract: This study evaluated the influence of water absorption and salt on dough rheological parameters used to discriminate gluten strength of bread wheat genotypes using a mixograph. The goal was to assess the need to optimize absorption which limits the efficiency of screening large sample sets of flour for breadmaking quality. Nineteen hard red winter wheat flours varying widely in absorption were evaluated using a 2-g micro-mixograph under conditions of constant and optimized (farinograph-based) absorption without and with salt, and were further evaluated in relation to gluten protein composition. Differences in discrimination of gluten strength between absorption protocols were small. Both procedures yielded dough development time and work input values that were highly correlated with HMW glutenin content and its ratio to soluble prolamins, but were poorly correlated with protein content. Using salt in dough mixing revealed significant genotype by salt interactions, and significantly increased dough development time and work input, but did not affect correlations to protein composition. Considering aspects of screening efficiency, relationships to protein composition, and the unpredictable effect of salt on gluten strength of different genotypes, it was concluded that the most effective procedure for efficiently evaluating gluten strength using the mixograph is to use constant absorption with salt. Highlights: Dough mixing protocols for screening gluten strength were evaluated using a mixograph. Optimized absorption was compared with 60% constant absorption ± salt. Varying dough mixing procedures minimally affected discrimination of gluten strength. Significant salt by genotype interactions were evident and were unpredictable. Gluten strength was closely related to ratio of HMW polymeric glutenin to soluble or total protein.